Investigations on lithium ion batteries for industrial applications - Tan, Ivan Fu Xing (Nanyang Technological University, 2023)
The relevance of lithium ion batteries has increased with the growth of the electric vehicle (EV) industry, and its widespread use in many of our electronic devices today. As with many other power storage solutions, the LIB likewise faces multiple challenges which we seek to understand and overcome. Aspects of the LIB which are constantly in need of improvement include charging times, storage and output capability, and battery safety. In the area of storage and output performance, several other factors like the design, production and application of the cell can substantially affect the output and battery life. With the understanding of these factors, solutions to improve LIBs range from new electrolytes and additives which improve SEI formation, changing electrode thickness and packing methods to influence the output or capacity and improve fire safety, to improving systems such as battery or thermal management systems. While the factors which affect the performance of LIBs are many, the focus here will be on design aspects of the cell with the application in mind and also the opportunity to delve into factors which are not yet well understood to further improve the process of cell making. Post-mortem studies will be done to attribute the effects of these factors to cell performance and to provide a more concrete understanding by complementing the earlier studies on this topic. This will bridge gaps between research and industrial environments, by applying the testing of batteries in a lab to a commercial scale. A better understanding of general battery making will be useful and highly applicable in the area of cell design, in view of the considerable reliance we currently have on LIBs, which is continuously growing.